Vector competence as an indicator of epidemic risk : yellow fever in Martinique, the Caribbean and America - (:unkn) unknown (My University, 2022)
Studying vector-borne diseases is of major interest for the Caribbean due to the presence of high densities of Aedes aegypti mosquito, the main vector of arboviruses. Martinique and the Caribbean have been subjected to repeated dengue epidemics for decades. The arrival and successive establishment of two new arboviruses, chikungunya (CHIKV) in 2013, and Zika (ZIKV) in 2015, has once again highlighted the importance of investigating vector-borne diseases and raised fears of the emergence of another arbovirus in the region, yellow fever virus (YFV). Originating in Africa, YFV was transported to the new world during the slave trade (15th - 19th century) and caused devastating epidemics, mainly in urban agglomerations. After more than two centuries of epidemics, yellow fever no longer rages in the Caribbean islands, and this was a consequence of the eradication program of the vector Ae. aegypti initiated at the beginning of the 20th century. The Caribbean seems to be spared by the virus since then, despite the omnipresence of Ae. aegypti in the islands (following the relaxation of control programs) and the presence of the virus in the tropical forests of South America and Trinidad circulates within an enzootic cycle. YFV belongs to the family Flaviviridae and genus Flavivirus, like DENV (dengue virus) and ZIKV. YFV is present in sub-Saharan Africa and South America (7 YFV genotypes described: 2 in America and 5 in Africa). The recent yellow fever epidemics in Angola in 2016 and more widely, in West Africa as well as those in Brazil in 2017 and 2018 indicate changes in the current distribution of the disease in tropical and subtropical regions of South America and Africa. Infected travelers ensuring multiple introductions into the islands raise fears of the occurrence of an epidemic initiated by an imported case. At a time when exchanges of travelers and goods are intensifying, the risk of introducing YFV into the Caribbean cannot be ruled out, as was the c
Keywords: African Research